2014
DOI: 10.1111/jsm.12463
|View full text |Cite
|
Sign up to set email alerts
|

To Say or not to Say: Dyadic Ambivalence over Emotional Expression and Its Associations with Pain, Sexuality, and Distress in Couples Coping with Provoked Vestibulodynia

Abstract: Introduction. Provoked vestibulodynia (PVD) is a highly prevalent and taxing female genital

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 60 publications
4
11
0
Order By: Relevance
“…Paired‐sample t ‐tests revealed that women had significantly higher scores on the CPAQ‐R than their partners ( t (60) = 3.51, P < 0.01). Additionally, consistent with previous research [50], women in the present sample were significantly more anxious ( t (60) = 4.53, P < 0.01) and depressed ( t (64) = 4.48, P < 0.01) and reported lower sexual functioning ( t (45) = −8.10, P < 0.01) than their partners. There was no significant difference in sexual satisfaction between women and their partners ( t (59) = −1.75, P = 0.09).…”
Section: Resultssupporting
confidence: 90%
“…Paired‐sample t ‐tests revealed that women had significantly higher scores on the CPAQ‐R than their partners ( t (60) = 3.51, P < 0.01). Additionally, consistent with previous research [50], women in the present sample were significantly more anxious ( t (60) = 4.53, P < 0.01) and depressed ( t (64) = 4.48, P < 0.01) and reported lower sexual functioning ( t (45) = −8.10, P < 0.01) than their partners. There was no significant difference in sexual satisfaction between women and their partners ( t (59) = −1.75, P = 0.09).…”
Section: Resultssupporting
confidence: 90%
“…Additionally, this study showed that both women with dyspareunia and their male partners who reported better dyadic sexual communication also reported better dyadic adjustment. This finding is in line with recent results from studies focusing on dyspareunia couples, showing that those who report low ambivalence over emotional expression or who talk more easily about personal topics such as sexuality, report better dyadic adjustment [22]. It also confirms findings from the chronic pain, communication and relationship literatures showing that better communication in general and better sexual communication in particular are associated with better dyadic adjustment in both women and men [25,26,32,34,54].…”
Section: Discussionsupporting
confidence: 90%
“…Couples' greater ambivalence over emotional expression (a marker of poor emotion regulation) has been associated with reductions in their sexual satisfaction and function, psychological adjustment, and relationship adjustment [73]. Furthermore, studies examining male partners' pain-related cognitions showed that their lower pain catastrophizing was associated with women's lower pain [74] and partners' greater pain acceptance was associated with their own lower incidence of depressive symptoms [75].…”
Section: Relationship Factorsmentioning
confidence: 99%
“…There have been repeated recommendations to include the partner in therapy given the interpersonal factors involved in women's sexual pain [81,73]. Cognitive-behavioral couple therapy (CBCT) for couples with vulvodynia is described as an integrative pain management and sex therapy intervention delivered to couples over 12 weekly 60-min sessions and includes psychoeducation, introduction of pain management techniques, communication skill building, sexual re-approach, discussion and development of sexual narratives, and mindfulness-and acceptance-based exercises [119].…”
Section: Psychosocial Treatmentsmentioning
confidence: 99%